Eksistensi Dā’iyah di Tengah Domestikasi Citra Diri Perempuan Shalihah: Perspektif Feminis Eksistensialis - Sholihah, Faridatus (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2018)
Being an empower women by actively showing her existence in the publicity is not easy. Moreover when it is related to leadership in the religion issues, where it is still dominated by men. This study aims to describe the existence that is fought by dā'iyah in the public space, whereas social construction holds them with domestication. This research uses descriptive qualitative methods. Techniques of collecting data by an in-depth interview, and validating by triangulation. The results show that “shalihah” concept is still closely related to domestic works, while the “imam” concept in the religion is still understood as a status that must be played by men. The criteria by sex are still in line with the quality of da’wah materials, da’wah methods, or even the knowledge of the missionary. So, dā'iyah feels a dilemma in carrying out their roles in the public and domestic space. For this reason, various strategies have been carried out by dā'iyah to maintain their existence.